EVALUASI IMPLEMENTASI PROGRAM ELECTRONIC KARTU TANDA PENDUDUK (E-KTP) DI KABUPATEN TEGAL DALAM MEWUJUDKAN ELECTRONIC GOVERNMENT (E-GOV) - Arrof Fefkhiatin .; purwoko astrika .; lusia astrika . (Journal of Politic and Government Studies, 2013)
AbstractIndonesian population growth is very significant in every year raises technical issues related to the experience of recording demographic data irregularities and inaccuracies. Various problems arise such us double KTP because of easier to make ID Card. By leveraging the internet and technology development as a breakthrough in realizing e-government, the government's was created elektronic identity cards (e-KTP) program which is based on the Decree of the President of the Republic of Indonesia Number 26 Year 2009 on the application of National Identity Card-Based Population By National Identification Number. Electronic ID card program was implemented in 2011 and is targeted for completion in 2012 is an effort to create an orderly administration through the Population Administration Information System (SIAK). From this, the authors would like to discuss about how to evaluate the implementation of e-ID card program in Tegal regency in realize e-government, if successful, less successful or unsuccessful and appropriate goals or not, then identify the driving factors of implementation, and is there any obstacles that occur during the implementation process.This research is an evaluative approach using qualitative and quantitative techniques of interviews, questionnaires, observation, and documentation. Sources of data obtained from primary data through interviews with key informants or persons, questionnaires with respondents executive group (tenaga operator e-KTP) and target groups (communities), observations by looking at the implementation of e-ID in the field. While secondary data from research documents related circuitry. Data analysis techniques with data reduction, tabulation, triangulation, and data verification.The survey results revealed a weakness in input and process indicators. E-KTP program based modern technology is not matched by the capacity of human resources who are competent so difficulty when faced with a disturbance in the computer and networking systems as well as their responsibility to serve the citizens in a timely fashion is not done. Socialization training to the candidates so that the operator is not notified in advance that the communication is not clear. Then the constraints associated with both the equipment and the technical problems in the recording process of the electronic ID card and the level of public awareness is low. However, the electronic ID card can be done in Tegal regency due to good coordination between agencies that are responsible for this program.Implementation of e-ID cards in less successful district look to the realization of electronic ID cards compulsory that only reaches 67.88%. Input and process of implementation of electronik ID card is not weak produce maximum outputs. Therefore, it is necessary to improve the quality of electronic ID equipment and internet networks as well as human resources who are competent in realizing e-government. Keywords: E-ID card, e-government, Implementation and Evaluation